Criticism of Capitalist Ideology in American Cinematic Representations: An Analysis of The Menu Film - Berama, Aditya Pria Niaga; Prihatika, Yusrina Dinar (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the representation of capitalist ideology in The Menu (2022) through a Marxist literary perspective. Specifically, the research aims to analyze how characterization, narrative structure, dialogues, and visual symbolism in the film construct critiques of class relations, labor exploitation, and capitalist ideology. Within the field of English literary and cultural studies, film can be analyzed as a narrative text that reflects social and ideological issues. While previous studies have explored symbolic and cultural aspects of the film, limited attention has been given to the representation of creative labor within a literary-critical framework. This study employs a descriptive qualitative method using narrative and symbolic analysis. The data consist of selected scenes, character dialogues, visual symbols, and narrative sequences obtained from The Menu (2022). Drawing on Karl Marx’s concepts of alienation and commodification, the analysis investigates how cinematic elements represent the relationship between creative labor and capitalist power structures. The findings reveal that the film portrays the transformation of creative labor into commodified objects within capitalist systems, resulting in alienation, class conflict, and the erosion of the intrinsic value of artistic work. The study contributes to English literary and cultural studies by demonstrating how contemporary cinematic texts function as sites of ideological critique and literary representation of capitalist social relations.